An Outsider's Perspective on Why We Climb Mountains and Why Projects Like the i5k Matter. Issue 4 (3rd July 2022) - Molik, David C
Abstract: Initiatives like the i5k are creating evermore genome assemblies. These initiatives are resource heavy, and their justifications and economics deserve attention. Scientifically, these initiatives are important, paving the way for cross-species analysis, requiring the building of new computational analysis and tools, and creating other new resources. However, an open question remains of how we quantitively measure the impact of genomes, and by extension these initiatives. This forum article discusses one such method which is to look at the publications about a species over time, however, this method does not show any signal from a published genome, leaving an open question of how to measure impact.